THE NARRATIVE OF A TEACHER AT THE NORMAL SCHOOL - Miranda, Luis Antonio Rabadán (Seven Editora, 2025)
Teaching represents a complex ethical, emotional, and intellectual endeavor, in which the teacher not only transmits knowledge but also shapes individuals capable of transforming their environment. The teacher is an essential agent in the motivation, self-esteem, and holistic development of students; their role becomes crucial when recognizing individual differences and promoting inclusive education. In this sense, the narrative of initial teacher training constitutes a process of personal and professional development that is enriched by experiences, reflections, and values acquired year after year of teaching practice. This work reflects on the trajectory of a special education teacher, Luis Antonio Rabadán Miranda, whose vocation was forged between initial doubt and the subsequent certainty of having chosen the right path. Through his experience at the Regional Center for Teacher Training in the State of Guerrero and his practice at a Support Unit for Regular Education (USAER) as his first workplace, the challenges and lessons learned from supporting students with disabilities and students facing Barriers to Learning and Participation (BLP) are highlighted. Teaching, in this context, is understood not only as instruction, but as accompaniment, inspiration and transformation, reaffirming that true teaching is built in daily practice and in the permanent commitment to diversity and educational justice. DOI: https://doi.org/10.56238/sevened2025.038-030